Exploring the electronic and magnetic properties of half-heusler alloy CoMnSb: implications for spintronics - Limbu, Binay; Dahal, Prem Sagar (BIBECHANA, 2025)
Heusler alloys have caught a lot of attention because they can be really useful in modern technology. In this study, we investigated the electronic and magnetic properties of CoMnSb by employing advanced computational methods rooted in Density functional theory and plane-wave pseudo potential approach. Our investigation uncovers that CoMnSb is a half-metallic ferromagnet with a half-metallic gap of 0 eV at the equilibrium lattice constant. The total spin magnetic moments have been computed 3µB per unit cell which is in good agreement with the slater pauling rule Mt = Zt − 18 for Half Heusler alloy. The hybridization of the eg and t2g orbitals of the Co, Mn,and P-orbitals of the Sb are primarily responsible for the band gap. This indicates that these alloys hold great potential as functional materials for spintronics.